2017
DOI: 10.1002/aoc.3917
|View full text |Cite
|
Sign up to set email alerts
|

Ag‐nanoparticle embedded p(AA) hydrogel as an efficient green heterogeneous Nano‐catalyst for oxidation and reduction of organic compounds

Abstract: P(AA)‐Ag heterogeneous catalyst system comprised of Ag nanoparticles embedded within hydrogel matrices has been described for the selective aerobic oxidation of alcohols and reduction of nitro phenols in water. P(AA)‐Ag nanocomposite was characterized by Fourier transform infrared (FT‐IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), thermal gravimetric analysis (TGA), X‐Ray photoelectron spectroscopy (XPS) and inductively coupled plasma atomic emission spectrometer (ICP). Cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This higher rate constant reveals that the catalytic reduction of 4‐NP is more feasible with a higher concentration of Pd/C‐dots. In comparison with those obtained by nanomaterial‐based catalysts, the as‐prepared Pd/C‐dots were found to show better catalytic efficiency (Table S2, Supporting Information) . The mechanism for the reduction of 4‐NP by Pd/C‐dots is shown in Scheme .…”
Section: Resultsmentioning
confidence: 94%
“…This higher rate constant reveals that the catalytic reduction of 4‐NP is more feasible with a higher concentration of Pd/C‐dots. In comparison with those obtained by nanomaterial‐based catalysts, the as‐prepared Pd/C‐dots were found to show better catalytic efficiency (Table S2, Supporting Information) . The mechanism for the reduction of 4‐NP by Pd/C‐dots is shown in Scheme .…”
Section: Resultsmentioning
confidence: 94%
“…Depending upon the PVA‐PHEMA ratio, the SPIONs accounted for 6–15% of the total mass of the gel. Metal ions can also bind with carboxyl groups loaded onto polymer chains forming nucleation sites, where upon introduction of a strong reducing agent, NPs can grow anchored to the hydrogel network . As such, the dimensions and porosities of the gel, as well as the concentrations of ions and reducing agents, may be tuned to obtain specific NP morphologies …”
Section: Methods and Effects Of Incorporating Inorganic Nps Into Drugmentioning
confidence: 99%
“…Metal ions can also bind with carboxyl groups loaded onto polymer chains forming nucleation sites, where upon introduction of a strong reducing agent, NPs can grow anchored to the hydrogel network. [66] As such, the dimensions and porosities of the gel, as well as the concentrations of ions and reducing agents, may be tuned to obtain specific NP morphologies. [67] The incorporation of NPs within a gel network can alter the mechanical properties of the hydrogel.…”
Section: Hydrogels Incorporating Npsmentioning
confidence: 99%
“…It is found that as recyclable heterogeneous catalyst, silver-based nanoparticles have high conversion and selectivity in alcohol oxidation or crosscoupling. [19][20][21][22] In order to improve the catalytic ability and recyclability of silver catalysts, many materials (hydrogel, cellulose, carbon fibers, magnetic materials, etc.) have been developed to support Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%